Visitors to nests of Hooded Vultures Necrosyrtes monachus in northeastern South Africa§. (31st August 2017) - Thompson, Lindy J; Davies, John P; Gudehus, Maja; Botha, André J; Bildstein, Keith L; Murn, Campbell; Downs, Colleen T
Abstract : Hooded Vultures Necrosyrtes monachus are critically endangered but little is known of their year-round use of nests or whether other species usurp Hooded Vulture nest sites. We investigated visitation rates by Hooded Vultures and other species (including potential nest predators and usurpers) to examine their effect on Hooded Vulture breeding success. We present observations of 33 species recorded by camera traps at 12 Hooded Vulture nests over a total of 93 nest-months (2 095 nest-days). Several pairs of Hooded Vultures visited their nests regularly during the non-breeding season, some adding nesting material, highlighting that pairs visited their nest(s) year round. Egyptian Geese Alopochen aegyptiaca, potential usurpers of raptor nests, were present at occupied and unoccupied Hooded Vulture nests, but we recorded no usurpation of nests by Egyptian Geese and they had no impact on vulture breeding success. Hooded Vulture breeding failure was linked to two species only: camera-trap imagery recorded one case of predation of a vulture egg by a Chacma Baboon Papio ursinus, and one case of a Martial Eagle Polemaetus bellicosus predating a vulture nestling. We recommend expanding the Hooded Vulture nest monitoring programme to include more pairs.